What distinguishes the strength and the effect of a Lewis acid: analysis of the Gutmann-Beckett method - Erdmann, Philipp; Greb, Lutz (Angewandte Chemie, 2022)
IUPAC defines Lewis acidity as the thermodynamic tendency for Lewis pair formation. This strength property was recently specified as global Lewis acidity (gLA), and is gauged for example by the fluoride ion affinity. Experimentally, Lewis acidity is usually evaluated by the effect on a bound molecule, such as the induced 31P NMR shift of triethylphosphine oxide in the Gutmann-Beckett (GB) method. This type of scaling was called effective Lewis acidity (eLA). Unfortunately, gLA and eLA often correlate poorly, but a reason for this is unknown. Hence, the strength and the effect of a Lewis acid are two distinct properties, but they are often granted interchangeably. The present work analyzes thermodynamic, NMR specific, and London dispersion effects on GB numbers for 130 Lewis acids by theory and experiment. The deformation energy of a Lewis acid is identified as the prime cause for the critical deviation between gLA and eLA but its correction allows a unification for the first time.
Gesehen am 06.10.2022